Science Learning Materials in Integrated PBL Scientific Literacy Model to Improve Problem Solving Ability of Junior High School Students - Eko Puji Lestari; Wasis Wasis; Tarzan Purnomo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This research is motivated by the low ability of students to solve problems. This research aims to produce the validity of the Problem Based Learning (PBL) model of science learning tools integrated with scientific literacy to improve the problem solving skills of class VIII junior high school students. The research method used is the development method with Four-D (4D) stages.The subjects of this study were validated learning tools including the syllabus, lesson plans (RPP), Student Worksheets, and problem-solving ability tests. While the object of this research is the level of validity of the learning device. The data analysis technique was carried out in a qualitative descriptive manner based on the assessment of three validators. The results of the validation by three validators concluded that the syllabus had an average score of 3.97 with valid criteria, the Learning Implementation Plan (RPP) had an average score of 3.84 with a valid category, Student Worksheet with an average score 3.70 in the valid category and the problem-solving ability test assessment instrument gets an average score of 3.60 in the valid category. Based on the results of this validity analysis, the learning materials developed was declared valid for use in learning. Thus the learning materials developed can be used as an alternative in improving the problem solving ability of students in their learning.